Quality of life in the informal economy: the street markets of the municipality of Ahome, Sinaloa - Armentilla Galaviz, Marisol (REVISTA CIENTIFICA GLOBAL NEGOTIUM, 2024)
Street markets, as a manifestation of the informal economy, represent a complex socioeconomic space where cultural traditions and economic opportunities intertwine. Despite their relevance in many communities, the quality of life of street market workers, characterized by precarious working conditions and social inequalities, has been little explored in academic research on the relationship between participation in informal economic activities, specifically in street markets, and the perception of quality of life of their workers. The objective of this research is to determine the correlation between participation in informal economic activities, specifically in street markets in the municipality of Ahome, and the perception of quality of life of their workers. As a methodology, a mixed research design was used, with an inductive and descriptive approach, to explore the relationship between participation in informal economic activities and the perception of quality of life. The sample consisted of 143 street market workers from the municipality of Ahome, selected through non-probabilistic convenience sampling. Data collection included a bibliographic review and the application of the WHOQOL-Bref instrument during field visits. Data were analyzed using IBM SPSS Statistics software, and the reliability of the WHOQOL-Bref scale was assessed using Cronbach’s Alpha coefficient. The results indicate that, despite the challenging socioeconomic conditions of street vendors, the perception of quality of life was found to be moderate to high, particularly in the psychological and social dimensions. A significant positive correlation was found between health perception and overall quality of life, suggesting that better physical health contributes to greater life satisfaction. Therefore, in conclusion, it is perceived that street vendors in Ahome, despite precarious working and economic conditions, report moderate to high levels of quality of life. This apparent paradox could be explained by factors such as strong social networks, a sense of community, and satisfaction derived from autonomy at work. However, it is important to highlight that there are areas of opportunity to improve their well-being, particularly in relation to health and access to basic services.